2017
DOI: 10.1093/ejcts/ezx032
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive or conventional edge-to-edge repair for severe mitral regurgitation due to bileaflet prolapse in Barlow’s disease: does the surgical approach have an impact on the long-term results?†

Abstract: A minimally invasive approach does not have a negative impact on the effectiveness and long-term durability of the EE repair for bileaflet prolapse in Barlow's disease. Long-term outcomes are excellent, and valvular performance remains stable over time with no evidence of mitral stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Of 1122 articles that were retrieved for evaluation, 18 met the inclusion criteria, including one randomized controlled trial, one propensity score matching study, 11 single-arm sternotomy studies, and five single-arm minimally invasive studies (Supplemental Figure 1). 7,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] There was 100% concordance between reviewers equating to a Cohen's k of 1. The mean sample size was 92.5 patients (range, 12 to 250) and the mean follow-up duration was 51.6 months (range, 14 to 138).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 1122 articles that were retrieved for evaluation, 18 met the inclusion criteria, including one randomized controlled trial, one propensity score matching study, 11 single-arm sternotomy studies, and five single-arm minimally invasive studies (Supplemental Figure 1). 7,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] There was 100% concordance between reviewers equating to a Cohen's k of 1. The mean sample size was 92.5 patients (range, 12 to 250) and the mean follow-up duration was 51.6 months (range, 14 to 138).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were no significant between-group differences in moderate mitral valve regurgitation recurrence and reoperation (minimally invasive vs sternotomy, 1.7% [95% confidence interval, 1.0% to 2.9%] vs 1.3% [95% confidence interval, 0.9% to 1.8%], P [ . 22). Patients in the minimally invasive group were exposed to significantly longer cross-clamp and cardiopulmonary bypass times (P < .01); however, there were no additional between-group differences in secondary outcomes.…”
mentioning
confidence: 99%
“…16 Propensity scores were estimated running multiple logistic models including various combinations of preoperative variables. The best balance was achieved with the following 10 variables: age at operation, sex, body mass index categorized as normal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) or not normal (<20 or >30), serum creatinine, atrial fibrillation, New York Heart Association class !III, ejection fraction, systolic pulmonary artery pressure, isolate P2 prolapse, and STS-PROM.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The majority of patients underwent valve repair through standard full sternotomy with-especially later in our series-limited midline skin incision (approximately 10-15 cm in length). Previous studies have demonstrated favourable results of the minithoracotomy approach to valve repair in patients with Barlow's disease [18,19]. However, this includes significant modifications of the mitral valve repair technique when compared with our technique.…”
Section: Discussionmentioning
confidence: 97%